Politics of memory : the Israeli Underground's struggle for inclusion in the national pantheon and military commemoralization - Lebel, Udi (Cass series--Israeli history, politics, and society ;, 2013)
"The production and management of public memory in Israel has been politicized through the efforts of successive Israeli governments. In the nascent years of the Israeli state, the ruling Labour Party sought to influence the collective memory of the people through selective production and collective assimilation of cultural practices associated with bereavement and commemoration. In tandem, efforts were made to fashion a ranking order of heroism and sacrifice through various means of memorialisation. Politics of Memory focuses on the struggle for inclusion in the domain of military commemoration by those barred from its patrimony and examines the effect of this struggle for the Israeli governments' legitimacy. A thought provoking study of the inclusion and exclusion processes of military commemoralization, and the effects of this for Israeli national identity, this book will be of interest to students and scholars of Israeli history, military studies and politics in general"--